If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 = 2x + -4 Reorder the terms: -18 = -4 + 2x Solving -18 = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -18 + -2x = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 -18 + -2x = -4 + 0 -18 + -2x = -4 Add '18' to each side of the equation. -18 + 18 + -2x = -4 + 18 Combine like terms: -18 + 18 = 0 0 + -2x = -4 + 18 -2x = -4 + 18 Combine like terms: -4 + 18 = 14 -2x = 14 Divide each side by '-2'. x = -7 Simplifying x = -7
| 2(4x^2-5)-[4(4x^2-1)+6]= | | 8-x=2x+14 | | F(x)=-2x^3-3 | | x*5=6000 | | (X+15)+20=90 | | 4x^2-4x-12=0 | | x*5=600000 | | 12(x+15)=13x+2 | | xe(xy)dy+ye(xy)dy=0 | | x*Y=600000 | | 4m=17m | | G(x)=-3x-3 | | x+5=6000 | | Y=2x^3-3x^2+x-6 | | -3+5v=-38 | | -2b-6+3b-2= | | 2.4c+6= | | 40+5x=5.00 | | Y=10x^3+7x^2+16x+3 | | 4(y-3)-6y=-26 | | 2x-6+108=180 | | 121k^2-36=0 | | 34=2x+10 | | 2x-7=3 | | -27x^3+8x=0 | | 0=x^2+16x-22 | | z+10+3x+30=180 | | 7+nx-6=31 | | z=12x+8y | | 3y+10=61 | | 3(x+2)-5=6x+1-3x | | 3y+10= |